Quality of Experience: A New Paradigm for Resource Management in Wireless Multimedia Networks - Piamrat, Kandaraj; Ksentini, Adlen; Viho, Cesar; Bonnin, Jean-Marie (Recent Patents on Computer Science, 2011)
Radio Resource Management (RRM) is especially crucial for wireless multimedia networking, where: (i) wireless resources are scarce and precious; (ii) multimedia applications impose a strong Quality of Service (QoS) support. In this context, Mobile Network Operators (MNO) have to find a trade-off between optimizing wireless resources (in terms of radio utilization), while ensuring QoS and hence increasing user satisfaction (or Quality of Experience - QoE). Traditional ways of managing radio resources, using information from monitoring technical parameters, fail to give accurate evaluations of user experience. Particularly, multimedia traffic should not be measured only in terms of throughput, loss rate, or delay but rather in terms of user experience. In this paper, we fill this gap by introducing a new paradigm for radio resource management (or RRM) based on QoE. We focus on the management of wireless environments at network side and without modification on user terminal. Further, we present several examples of user's case to demonstrate how MNO can use QoE to handle three important issues related to RRM, namely access (admission) control, physical rate adaptation, and packet scheduling in wireless environment. The obtained results are encouraging and open a wide range of research directions. Finally, this paper also provides a review on recent patents in the field of Quality of Experience over wireless networks.
Keywords: Admission control